Benigno Ramos and the Sakdal Movement - Terami-Wada, Motoe (Philippine Studies, 1988)
An earlier article (Philippine Studies [1988]: 131-50) outlined the growth of the Sakdal Movement from 1930-1934. This present article discusses the life of Benigno Ramos, who was largely responsible for the success of the Sakdal Movement, which left its mark on the 1930's.